TINGKAT KESUKAAN DAN SENYAWA PENYUSUN EKSTRAK FLAVOR DAUN SALAM (EUGENIA POLYANTHA WIGHT.) DARI BEBERAOA METODE SEPARASI - Wartini Harijono, Ni Made; Susanto, Tri; Rurini Retnowati, Yunianta (Agrotekno, 2008)
The research was conducted to produce salam leaf extract flavor, and to determine the composition of its flavor compounds, and to know the preference. The experiment was undertaken by using a randomized block design. Three methods of the separation process were undertaken, namely steam distillation, water distillation and simultaneous distillation-extraction. Fresh salam leaf were cutted and extracted by three methods and the flavor extract was drying by MgSO4 anhydrate. The flavor extract were determined its yield and characteristic of sensory and analyzed by gas chromatography-mass spectrometry (GC-MS). The research result showed that the most preferred was the salam leaf flavor extracted by the simultaneous distillation-extraction method. Its flavor extract was contained the main compound of ?-ocimene (9.04%), octanal (11.31%), cis-4-decenal (28.43%), ?-humulene (9.20%) and decanal (6.49%).